ONLINE TUTORING FOR LANGUAGE LEARNING (Journal of Foreign Language Studies, 2024)
Teaching foreign languages is not new in Vietnam; but teaching and learning foreign languages online under the instruction of a tutor is a novel experience which is currently being applied in some well-known universities which specialize in foreign language teaching or is implemented in private companies which sell online learning accounts to individual learners. This article focuses on four main points: (1) basic concepts of e-learning and online tutoring; (2) components of a learning management system (LMS); (3) roles of tutors in e-learning foreign languages; (4) suggestions and recommendations of e-learning activities in Vietnam. Some studies on online tutoring in Vietnam generally as well as within the scope of the National Foreign Languages Project 2020 particularly are mentioned in the last section